Innovative Marketing Strategies for the Development of Tourism in Romania - Alexandra Popa; Alina-Elena Ionascu; Dana Nicoleta Domolescu (Ovidius University Annals: Economic Sciences Series, 2021)
The development and implementation of a strategic plan can be seen as the most important activities undertaken in any business or by any public or private sector organization. Strategic decisions are the key decisions that must be made by any organization; and a number of more detailed operational decisions can be made from the strategic decisions that set the framework. Implementing the established strategies will determine the eventual long-term success or failure of the organization. In every service sector, every organization needs to look at ways to attract consumers to buy the services they offer. This is also applied in the tourism industry where every organization should be creative in its marketing approaches and be more innovative in all its actions. Technological progress has permitted access on the market to many autonomous suppliers and is allowing consumers to make purchasing decisions based on the total experience of a destination, therefore tourism marketing has become increasingly difficult over the past few years. In this article, our aim is to highlight the importance of using innovative marketing strategies as a way to attract customers (in this case, represented by tourists) and develop the tourism sector in Romania.